Influence of E-Service Quality, Promotion, and Brand Trust on Application Use Decisions - Nabila Firda Alfani; Rustono - Rustono; Nur - Rini (JOBS (Jurnal Of Business Studies), 2023)
One of the Central Java pawnshops is having trouble because compared to people who do business there directly, the number of consumers who have registered as active users and are transacting through the Pegadaian Digital Service is comparatively low. This study intends to determine the effects of e-service quality, promotion, and brand trust on customers' decisions to utilize the Pegadaian Digital Service application at one Central Java pawnshop. Purposive sampling was employed to gather the data, with a sample of 302 consumers from a Central Java pawnshop who had been using the Pegadaian Digital Service app for the previous six months. Heteroskedasticity, multicollinearity, and normality tests are a few of the analysis techniques employed. The analysis techniques employed include the coefficient of determination, the t-test, the f-test, the heteroskedasticity test, the linearity test, the multiple linear regression analysis, and the normality test. The results of this study show that advertising, brand trust, and the caliber of e-services all have a beneficial influence on usage choices. The findings of this study demonstrate that brand trust, e-service quality, and advertising all positively impact usage decisions. According to the coefficient of determination data, e-service quality, promotion, and brand trust all together account for 60,2% of the usage choice. The remaining proportion, 39,8%, shows how much the study is impacted by other factors that were not addressed